Peripapillary and macular microvasculature in neovascular age-related macular degeneration in long-term and recently started anti-VEGF therapy versus healthy controls - Türksever, Cengiz; Hoffmann, Laura; Hatz, Katja (Frontiers in Medicine, 2023)
Aim To investigate the peripapillary and macular microvasculature in neovascular age-related macular degeneration (nAMD) in recently started versus long-term anti-vascular endothelial growth factor (VEGF) therapy and healthy controls. Methods Eyes with nAMD treated in a treat-and-extend regimen were assigned to group 1 (<5 injections) or 2 (≥20 injections) whereas group 3 constituted the healthy age-matched controls. Blood flow signals were acquired using PLEX® Elite 9000 swept-source optical coherence tomography angiography (OCTA) of the macular and peripapillary regions. Mean ganglion cell complex (GCC) thickness values were quantified using spectral-domain optical coherence tomography (SD-OCT). Results Including 80 eyes whereof 40 controls, macular superficial perfusion density was significantly reduced in group 1 and 2 compared to controls (p < 0.001; p = 0.010) without a difference between groups 1 and 2. Peripapillary perfusion parameters did not correlate with post-operative intraocular pressure (IOP) or number of anti-VEGF injections. Mean peripapillary flux index was significantly lower in group 2 than in controls (p = 0.023) and significantly decreased in the nasal quadrants for both AMD groups compared to group 3 (p = 0.013; p < 0.001). Mean peripapillary perfusion density was significantly reduced in both AMD groups compared to controls (0.515 ± 0.02 versus 0.556 ± 0.03, p < 0.0001). Conclusion Frequency of anti-VEGF treatment in nAMD and post-operative IOP showed no correlation with peripapillary perfusion parameters, but anti-VEGF treated nAMD patients exhibited partly altered peripapillary perfusion compared to healthy controls. Reduced macular perfusion density of the inner retina in anti-VEGF treated nAMD compared to healthy controls might be discussed as an anti-VEGF treatment effect or a characteristic of nAMD.